The Action for Breach of Promise of Marriage in Early Colonial New Zealand: Fitzgerald v Clifford (1846) - Simpson, Megan (Victoria University of Wellington Law Review, 2010)
In 1846, the first breach of promise of marriage case was heard by the Supreme Court of New Zealand. Unlike many other breach of promise cases heard throughout the Empire during the nineteenth century, this case was not publicly reported. Rather, it is a case that exists only within the pages of Justice Chapman’s judicial notebook, absent from the newspaper court reports of the time. This action was relatively rare in the colony but the testimonies of witnesses examined enable us to gain an insight into matters of class, courtship, family, reputation and social protocols in the mid-nineteenth century. This paper considers the legal history of the action in New Zealand from 1842-1875, focussing on the case of Fitzgerald v Clifford (1846) to explore how private matters of courtship and romance became matters of legal and sometimes public debate.